Synthesis, characterizations and anti- corrosion screening of salpphen and salophen / Nur Syahirah Mohd Nordin - Mohd Nordin, Nur Syahirah (2017)
N,N-bis(salicylidene)-p-phenylenediamine (Salpphen) and N,N-bis(salicylidene)-o-phenylenediamine (Salophen) which known as Schiff base ligand were synthesized from the reaction between salicylaldehyde and each p-phenylenediamine and o-phenylenediamine respectively. From the melting point measurement, it showed significant differences because Salpphen is more stable with melting point at 214 °C, while Salophen is less stable with melting point at 165 °C. The elemental analysis exhibit close values between experimental value and theoretical value. The IR spectrum of Salpphen detected the frequency vibrations of v(C=N) at 1609 cm-1 and v(p-substitute) at 828 cm-1, while the spectrum of Salophen detected the frequency of v(C=N) at 1612 cm-1 and also v(o-substitute) at 760 cm-1. These data indicated the formation of azomethine group and different substituents positions on the benzene ring. Finally, the UV-Visible spectra of both ligands showed the n-π* transition which also confirmed the formation of Schiff base ligand through the azomethine group. The anti-corrosion screening was done at various inhibitor concentrations in 1 M hydrochloric acid (HCl) diluted from 37 % of HCl. The screening was done in the presence and absence of inhibitor to compare the ability of Schiff base ligands to act as corrosion inhibitor on mild steel. The results show that Salpphen was better inhibitor of corrosion compared to Salophen due to the different of substituents position in the benzene ring from amine used because Salpphen provide greater stability. Therefore, Salpphen was found to exhibit better protection on the mild steel from corrosion in acidic condition.